A Bismuth‐Based Metal–Organic Framework as an Efficient Visible‐Light‐Driven Photocatalyst. Issue 6 (8th December 2014) - Wang, Guanzhi; Sun, Qilong; Liu, Yuanyuan; Huang, Baibiao; Dai, Ying; Zhang, Xiaoyang; Qin, Xiaoyan
Abstract A visible‐light‐responsive bismuth‐based metal–organic framework (Bi‐mna) is demonstrated to show good photoelectric and photocatalytic properties. Combining experimental and theoretical results, a ligand‐to‐ligand charge transfer (LLCT) process is found to be responsible for the high performance, which gives rise to a longer lifetime of photogenerated charge carriers. Our results suggest that bismuth‐based MOFs could be promising candidates for the development of efficient visible‐light photocatalysts.